Posted by **Cyndy f** on Tuesday, May 22, 2012 at 12:23pm.

Suppose that f(A,B,C) means A-2C + (1/2)AB

A. Find f(2,3,-11)

B. Find f(D,5,D)

C. Find f(3,4,f(-5,7,4))

- Math -
**Reiny**, Tuesday, May 22, 2012 at 12:45pm
just do what it says...

f(A,B,C) = A-2C + (1/2)AB

f(2,3,-11) = 2 -2(-11) + (1/2)(2)(3)

= 2 + 22 + 3 = 27

f(D,5,D) = D - 2D + (1/2)(D)(5)

= D - 2D + (5/2)D = (3/2)D or 3D/2

for the last one,

f(-5,7,4) = ?

then f(3,4,? ) = ....

you try it.

## Answer This Question

## Related Questions

- Math - Suppose the modiefied quota is 5.37. Find the lower quotas and the upper ...
- Trignometry - Given Triangle ABC: I think there are suppose to be right ...
- algebra - Suppose f(x)=Ax+B for real constants A and B. If f(60)=70 and f(72)=79...
- Calculus - Suppose the total area under the curve y=x^2-mx+1 from 0 to 5 is 11....
- Algebra1 - Please let me know if these are correct. 1. Find: 10% of 30 3 2. Find...
- Math - Suppose that for any integer n, f(n)= (n-1). if n is even; f(n)= (2n). if...
- competition - if means '¡Á' ,'q' means'-' , 'r' means ' ' 's' means '¡Â' then ...
- math - The heights in inches of 18 randomly selected adult males in LA are ...
- Math - Suppose f (x) = x^3 + x and g(x) = f^-1(x). Find g'(2). I am confused ...
- math - suppose x S f(t) dt= x^2 - 2x + 1. Find f(x). 1 S = integral and 1 = ...

More Related Questions